2020
DOI: 10.1126/sciadv.aay3051
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a regulates extracellular vesicle secretion from prostate cancer cells via targeting SHC4, PFDN4, and CHORDC1

Abstract: Extracellular vesicles (EVs) are involved in intercellular communication during cancer progression; thus, elucidating the mechanism of EV secretion in cancer cells will contribute to the development of an EV-targeted cancer treatment. However, the biogenesis of EVs in cancer cells is not fully understood. MicroRNAs (miRNAs) regulate a variety of biological phenomena; thus, miRNAs could regulate EV secretion. Here, we performed high-throughput miRNA-based screening to identify the regulators of EV secretion usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Furthermore, we searched some of the relevant public databases (GSE32448, 46602, and 55945) and found that miR‐1908 was downregulated in PCa tissues (Figure D). Intriguingly, based on this miRNA screening, we could not see any suppressive effect of EV secretion in 22Rv1 cells by miR‐26a, which was the most effective miRNA for suppression of EV secretion in PC3M 8 . Likewise, miR‐1908 was not an EV suppressive miRNA in PC3M cells (Figure E).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Furthermore, we searched some of the relevant public databases (GSE32448, 46602, and 55945) and found that miR‐1908 was downregulated in PCa tissues (Figure D). Intriguingly, based on this miRNA screening, we could not see any suppressive effect of EV secretion in 22Rv1 cells by miR‐26a, which was the most effective miRNA for suppression of EV secretion in PC3M 8 . Likewise, miR‐1908 was not an EV suppressive miRNA in PC3M cells (Figure E).…”
Section: Resultsmentioning
confidence: 82%
“…miRNAs through their dysregulated profiles function as regulators of both tumor progression and suppression in almost all types of cancer 7 . We have shown previously by comprehensive miRNA screening that miRNAs can regulate EV secretion in cancer cells 8 . In this study, 2 metastatic PCa cell lines, PC3 and PC3M, were employed; we found that miR‐26a regulates EV secretion in these cell lines through suppression of SHC4, PFDN4, and CHORDC1 8 .…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations